Gut microbiome and response to checkpoint inhibitors in non-small cell lung cancer—A review. (January 2020) - Nagasaka, Misako; Sexton, Rachel; Alhasan, Roba; Rahman, Sarah; Asfar, Azmi S.; Sukari, Ammar
Highlights: The gut microbiome plays an important role in host immune response. Alterations in lung bacterial content may influence COPD and asthma. Gut microbiota has shown to alter effects of cancer therapy in murine models. NSCLC patients responding to checkpoint inhibitors had higher microbiome diversity. Best approaches to modulate the gut microbiome are under investigation. Abstract: The gut microbiome is a collection of diverse bacteria that normally reside within the gastrointestinal tract. In recent years, the relationship between the gut microbiome, and fluctuations in it, and overall health has been an intense area of interest in medical research. In addition to having a barrier role in the gastrointestinal tract, there appears to be an immune function of gut microbiota, with a correlation between dysbiosis of gut microbiota and certain inflammatory and malignant disease states of the gastrointestinal system. We have also seen evidence that the gut microbiome can impact response to immunotherapy in melanoma patients. Evidence has also emerged to show that the lung has a microbiome of its own. In this review we will explore the relationship between the gut and lung microbiomes, known as the gut-lung axis, and the potential effects of this axis on anticancer therapy in lung cancer, including checkpoint inhibitors.